Športni turizem po pandemiji COVID-19 - Loborec, Vesna (Šport (Ljubljana), 2021)
The article presents sports tourism, its development and significance after the Covid-19 pandemic. Sport has always played an important role in the tourist offer. In the future it is expected that in order to recover from the pandemic, tourists will want to experience active, safe and green holidays by including outdoor sports activities. As soon as the restrictions on movement, sports activities and travel are lifted, the need for outdoor activities will increase greatly. Tourists will look for destinations in nature, in beautiful surroundings and not so much in big cities. The demand for "green and safe" destinations has already increased significantly during the pandemic, but it is expected to grow further.
Keywords: COVID-19; epidemic; epidemije; korona virus; pandemic; pandemije; sport; šport; tourism; turizem